A Preliminary Study for Ultraviolet Optical Methyl Salicylate Monitoring in Agriculture - Ivana Di Bari; Domenico Longo; Giuseppe D’Arrigo; Gaetano Giudice; Antonella Sciuto (Sensors)
Methyl Salicylate, commonly known as wintergreen oil, is a volatile organic compound which plays a crucial role in agriculture as a signaling compound for plant defense mechanisms and as an attractant for beneficial insects. Rapid and accurate detection of Methyl Salicylate is pivotal for understanding plant responses to stress and plant-to-plant communication, and it is crucial for pest management. In this work, we propose a proof of concept for Methyl Salicylate detection in agriculture, exploiting a solid-state sensor technology. Our attention is focused on the monitoring of the second characteristic Methyl Salicylate optical absorption peak, at about 310 nm. To achieve this, we developed an optical sensing apparatus comprising a UV source, a silicon carbide visible-blind UV detector, and a chamber with a 16 cm optical path. This configuration enables testing of various Methyl Salicylate concentrations and achieves a detection limit as low as 70 ppb at room temperature. Preliminary cross-testing with Methyl Jasmonate demonstrated selectivity for Methyl Salicylate, confirming the sensor’s specificity. Additionally, a design for a compact and handheld system for on-site volatile organic compound monitoring in the agricultural field is also proposed.